Effect of aqueous Fe(II) on Sb(V) sorption on soil and goethite. (March 2016) - Fan, Jian-Xin; Wang, Yu-Jun; Fan, Ting-Ting; Dang, Fei; Zhou, Dong-Mei
Abstract: The effects of Fe(II) on the sorption and precipitation of Sb(V) on soils and goethite were investigated using batch experiments and X-ray photoelectron spectroscopy (XPS) in this study. The sorption capacity of Sb(V) were much higher in anoxic soil than oxic soil. Typically, dissolved Fe(II) concentration in anoxic soils decreased significantly with increasing Sb(V), which may be suggestive of Fe–Sb precipitation. The elevated concentrations of Fe(II) (1 mM) enhanced the sorption capacity of Sb(V) on goethite significantly. However, synchrotron radiation X-ray diffraction showed no new characteristic peak, indicating that this Fe–Sb precipitate might be poor crystallinity or amorphous. Moreover, Sb(III) was detected in anoxic soil, and the reduction of Sb(V) to Sb (III) improved the sorption capacity of Sb in anoxic soil because of the low solubility and migration of Sb(III). Nevertheless, Fe–Sb co-precipitation and Sb(V) reduction to Sb(III) might contribute simultaneously to the increased sorption capacity of Sb(V) on anoxic soils. This research could improve our current understanding of soil Sb chemistry in paddy and wetland soils. Graphical abstract: Highlights: Sorption capacity of Sb on reduced soil was much higher than that on oxic soil. Aqueous Fe(II) can enhance the sorption capacity of Sb on soil and goethite. XPS were used to gain speciation of Sb and Fe in soil and goethite.